Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.51381/adrs.v3i2.35
|View full text |Cite
|
Sign up to set email alerts
|

American Privacy Perceptions in the COVID Pandemic

Abstract: The on-going COVID-19 pandemic has brought surveillance and privacy concerns to the forefront, given that contact tracing has been seen as a very effective tool to prevent the spread of infectious disease and that public authorities and government officials hope to use it to contain the spread of COVID-19. On the other hand, the rejection of contact tracing tools has also been widely reported, partly due to privacy concerns. We conducted an online survey to identify participants’ privacy concerns and their ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…A study based on COVID-19 cases in Singapore 51 confirmed that enhanced surveillance and contact tracing help reduce transmission. On the other hand, close surveillance can raise public concerns because of the possible stigmatization, discrimination 52 and privacy issues 53 , 54 it can entail. The current crisis uncovered the weakness of disease surveillance in almost all countries characterized by weak public communication 53 , poor contact tracing 55 and incomplete and inaccurate data 56 .…”
Section: Discussionmentioning
confidence: 99%
“…A study based on COVID-19 cases in Singapore 51 confirmed that enhanced surveillance and contact tracing help reduce transmission. On the other hand, close surveillance can raise public concerns because of the possible stigmatization, discrimination 52 and privacy issues 53 , 54 it can entail. The current crisis uncovered the weakness of disease surveillance in almost all countries characterized by weak public communication 53 , poor contact tracing 55 and incomplete and inaccurate data 56 .…”
Section: Discussionmentioning
confidence: 99%